The Role of the primary school in the Qassim educational region in activating the practices of the green school from the point of view of the teachers - Alharbi, Maha Dahlos; Alhodaif, Najla Mohammed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the role of the primary school in the Qassim educational region in activating the practices of the green school from the point of view of the teachers, by standing on the reality of the role of the primary school in activating the practices of the green school from the point of view of the teachers, and to identify the most important obstacles to the application of green school practices in the primary school from the point of view of teachers. The study used the descriptive approach in a survey style, and the questionnaire tool was applied to collect the study data, and the questionnaire consisted of two axes, namely (the reality of the primary school’s role in activating green school practices from the teachers’ point of view, obstacles to applying green school practices in primary school from the female teachers’ point of view), and it included On 39 phrases, divided by 23 phrases for the first axis and 16 phrases for the second axis, the study sample consisted of (328) female primary school teachers in the city of Buraidah in the Qassim region, and the data was analyzed using the SPSS statistical package program. The study reached a number of results, the most important of which are: - The reality of the primary school’s role in activating the green school practices from the teachers’ point of view is largely achieved, with a mean weight of 3.667 and a standard deviation of 1.239. - Obstacles to applying green school practices in primary school from the point of view of female teachers, with a mean weight of 3.587 and a standard deviation of 1.233. In results of the study, the researcher presented a number of recommendations and suggestions for future studies.